SYNTHESIS OF NEW AZODYES FOR DYEING OF COTTON AND POLYMER MATERIALS - Polya Miladinova; Natali Tsvetanova; Petranka Naydenova-Marinova (Journal of Chemists, Technologists and Environmentalists)
New orange and magenta dyes, containing a residue of 4,4`-diaminostilbene-2,2`-disulphonic acid and allylic groups in their molecule have been synthesized. They were evaluated for applicability on cotton, and samples with intensive colour have been obtained. The degree of exhaustion, fixation and the optical properties from the CIE Lab colour space have been examined. The photostability of the dye in solution and dyed textile material was determined. The possibilities for copolymerization of the dyes with acrylamide and acrylonitrile have been investigated and intensive coloured, stable on different solvents polyacrylamide and polyacrylonitrile have been obtained. From the obtained results it can be concluded that the synthesized dyes are suitable for colouration of cotton and polymer materials as well as giving them UV protective properties.